1993
DOI: 10.1007/bf02009381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pooled and individual components ofBordetella pertussis as antigens in an enzyme immunoassay for diagnosis of pertussis

Abstract: Six different antigen preparations for use in an enzyme immunoassay (EIA) to detect IgM, IgA and IgG antibodies to Bordetella pertussis were evaluated using sera from 13 randomly selected culture-positive patients and from 87 patients with suspected pertussis during a pertussis outbreak. Based on results in 80 healthy control sera a specificity limit of 99.9% was selected. Sera from all culture-positive patients reacted with at least one of the antigens. The sensitivity of the EIA using the individual antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Like Mertsola et al , 10 , 11 , 12 , 13 we found a high level of pre‐existing placentally acquired antipertussis IgG, which was not unexpected during a period in which pertussis was epidemic. This affects the magnitude of the vaccine response, as measured in the whole‐cell ELISA assay if only the fold‐increase in IgG index is considered.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Like Mertsola et al , 10 , 11 , 12 , 13 we found a high level of pre‐existing placentally acquired antipertussis IgG, which was not unexpected during a period in which pertussis was epidemic. This affects the magnitude of the vaccine response, as measured in the whole‐cell ELISA assay if only the fold‐increase in IgG index is considered.…”
Section: Discussionsupporting
confidence: 81%
“…Few studies have been published on the use of whole‐cell ELISA to measure pertussis antibodies. Mertsola and colleagues 10 , 11 , 12 , 13 have assessed the performance of whole‐cell ELISA in a number of pertussis outbreaks and have compared that assay with single‐antigen assays and with ELISA assays that use a pool of purified antigens. Their conclusion was that the antipertussis IgG measured in a whole‐cell ELISA is quite likely to be high in the ‘acute’ phase blood sample of vaccinated individuals, and that IgG seroconversions are therefore not commonly detected, even if there is a rise in pertussis IgG antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, these ELISAs use purified antigens, although the use of mixed antigens has also been described (8,13,18). The availability of an international reference preparation for pertussis serology has increased the comparability between ELISAs (24).…”
Section: Discussionmentioning
confidence: 99%
“…The study subjects included 125 patients (50 males; age range 1–71 years; median, 15 years; age groups: ≤10 years n = 38, 11–18 years n = 38, and >18 years n = 49) randomly selected from serologically diagnosed pertussis patients at the Department of Medical Microbiology and Immunology, the University of Turku in 2004 (Table ). The diagnosis was based on the IgM and IgA antibody levels measured by ELISA using sonicated B. pertussis bacteria as a coating antigen . The diagnosis was further confirmed with a pertussis toxin (PT)‐based ELISA at our Pertussis Reference Laboratory, National Institute of Health and Welfare, Turku, Finland.…”
Section: Methodsmentioning
confidence: 99%